The key to Rondo - Rodda, Emily (Scholastic Press, 2008)
Through an heirloom music box, Leo, a serious, responsible boy, and his badly-behaved cousin Mimi enter the magical world of Rondo to rescue Mimi's dog from a sorceress, who wishes to exchange him for the key that allows free travel between worlds.